Incidence of coronary aneurisms in Pediatric Inflammatory Multisystemic Syndrome caused by COVID-19: A systematic review (Research, Society and Development, 2021)
Coronary aneurysms are dilations in an arterial segment. Such changes were already due to certain known pathologies. However, with the arrival of the pandemic caused by COVID-19, there was an increase in cases of children with coronary aneurysms when associated with the Pediatric Inflammatory Multisystemic Syndrome caused by SARS-CoV-2, called PIMS-TS. The present study aims to analyze the incidence of coronary aneurysms in Pediatric Inflammatory Multisystemic Syndrome caused by COVID-19. 22 original articles related to the theme, between 2020 and 2021, in English and Portuguese, were analyzed through the databases of PubMed, LILACS, Google Scholar and SciELO. The exclusion criteria used were: Books, dissertation project documents, abstracts at events, editorials, literature reviews, isolated case reports, articles that did not meet the inclusion criteria and duplicate articles. In view of the analyzed studies, it is concluded that the incidence of coronary aneurysms occurs through the PIMS-TS. The lowest incidence rate found was 2.3%, the highest, 79.92%, with an overall average of ± 17.34%.